2020
DOI: 10.1017/s026646742000019x
|View full text |Cite
|
Sign up to set email alerts
|

Can an exotic tree (Jackfruit, Artocarpus heterophyllus Lam.) influence the non-volant small mammals assemblage in a protected area of Atlantic Forest?

Abstract: Jackfruit (Artocarpus heterophyllus Lam.) is an exotic invasive plant species in the Brazilian Atlantic Forest that causes changes in the environment through the release of allelopathic substances and has high fruit production. We aimed to understand the potential effects of the jackfruit on the non-volant small mammal assemblage in an area protected by law, in the municipality of Cariacica – Espírito Santo, south-eastern Brazil. We sampled the small mammals assemblage using live traps in 18 sites, eight with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…Artocarpus heterophyllus , reported to be invasive in 24 other countries, has been studied most in Brazil's Atlantic forests, where its invasiveness and negative impacts are well demonstrated and removal has been proposed (Abreu & Rodrigues, 2010; Bergallo et al, 2016; Gama‐Matos et al, 2021; Moura et al, 2020). In east Africa, it has been reported as invasive is the East Usambara mountains (Sheil, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Artocarpus heterophyllus , reported to be invasive in 24 other countries, has been studied most in Brazil's Atlantic forests, where its invasiveness and negative impacts are well demonstrated and removal has been proposed (Abreu & Rodrigues, 2010; Bergallo et al, 2016; Gama‐Matos et al, 2021; Moura et al, 2020). In east Africa, it has been reported as invasive is the East Usambara mountains (Sheil, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…The challenges posed by invasive exotic species to the conservation of biological diversity are well documented (D'Antonio & Meyerson, 2002; Gentili et al, 2021; IPBES‐IPCC, 2021; Kulmatiski, 2006). Exotic species reduce indigenous diversity, establish persistent communities that make a return of displaced indigenous species communities difficult and alter ecosystem processes and functions (Dueñas et al, 2021; Gama‐Matos et al, 2021; Stewart et al, 2021). Invasive exotic species may pose economic costs which can be too heavy to manage (Nampala, 2020; Syliver et al, 2020; Warziniack et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In Neotropical forests, many species with distinct characteristics are able to invade and cause different types of impacts in a wide range of ecosystems. In closed-canopy forests, the invasive tree Artocarpus hererophyllus is reported affecting both plant and animal native communities Gama-Matos et al 2020), as well as the herbaceous Tradescantia zebrina that is commonly found in understories of protected forests .…”
Section: Introductionmentioning
confidence: 99%